Implementation of Artificial Intelligence in Zakat Management: A Predictive Management Model for Empowering Mustahik in Digitally Disadvantaged Cities - Hasan Syahrizal (PT. Hassan Group Publisher, 2025)
The use of Artificial Intelligence (AI) in zakat management has become a strategic issue in optimizing distribution and empowering mustahik in the digital era. The purpose of this study is to analyze the implementation of AI in zakat management by developing a predictive management model relevant to digitally disadvantaged cities. This research employs a qualitative approach with a descriptive-analytical design through a systematic literature review of international articles, global institutional reports, and case studies of zakat organizations adopting digital innovation. The findings indicate that AI implementation can enhance efficiency, transparency, and distribution accuracy while simultaneously confronting challenges related to infrastructure, digital literacy, and cultural acceptance. The implication of this study highlights that an AI-based predictive model can transform zakat from short-term relief into a sustainable empowerment instrument consistent with the Islamic value of justice